The health terminology project glossaries` structure - Marini, Sátia (2014)
Current paper was motivated by a Master´s degree in Translation Studies on one of the glossaries of the Health Terminology Project (PTS) of the Ministry of Health (MS) inBrazil, by which the products developed by the project were analyzed. The authors would like to forward their experience earned from the development of these instruments and from the evolution of the glossary´s layout and structure. Although within the same institution, each instrument is made suitable to the specific purpose of each area and the terminology project accumulates experience by the constant improvement of previously developed glossaries (adding new terms; providing the equivalent word in other languages for terms already defined) and by the establishment of new ones. The evolution of the structure of the glossaries was qualitatively analyzed; remarks on the types of cross references were made; a quantitative survey of their main features was undertaken. Finally, the importance of this type of work should be underscored either within the government, or in the academy or in private companies, for the sharing of intellectual knowledge.